2018
DOI: 10.1021/acs.jafc.8b00726
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Dietary l-Arginine and N-Carbamylglutamate Supplementation on Intestinal Integrity, Immune Function, and Oxidative Status in Intrauterine-Growth-Retarded Suckling Lambs

Abstract: This study investigated the effects of dietary l-arginine (Arg) and N-carbamylglutamate (NCG) supplementation on intestinal integrity, immune function, and oxidative status in intrauterine-growth-retarded (IUGR) suckling lambs. A total of 48 newborn Hu lambs of normal birth weight (CON) and IUGR were allocated randomly into four groups of 12 animals each: CON, IUGR, IUGR + 1% Arg, or IUGR + 0.1% NCG. All lambs were raised for a period of 21 days from 7 to 28 days after birth. The Arg or NCG group exhibited imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 51 publications
6
54
0
Order By: Relevance
“…Western Blotting. Total protein was extracted, and the concentration was determined as previously described [32]. Afterward, 50 μg total proteins was mixed with the loading buffer, followed by 5 min of denaturation at 100°C.…”
Section: Gene Expression Detected By Real-time Pcr (Rt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Western Blotting. Total protein was extracted, and the concentration was determined as previously described [32]. Afterward, 50 μg total proteins was mixed with the loading buffer, followed by 5 min of denaturation at 100°C.…”
Section: Gene Expression Detected By Real-time Pcr (Rt-pcr)mentioning
confidence: 99%
“…Also, L-Arg and NCG have been shown to protect the liver against lipid peroxidation [26][27][28] as well as play a key role in inflammatory response regulation [29]. Our team conducted a series of studies on Hu sheep, a prolific and precocious native breed in China, where L-Arg and NCG were fed to either underfed ewes from day 35 to day 110 of gestation [18,21,30,31] or to IUGR lambs in the period from day 7 to day 28 after birth [32]. Results of these study series revealed the capability of L-Arg and NCG to enhance fetal and placental development and antioxidant capacity [21]; ameliorate fetal growth retardation in underfed ewes [30]; improve the amino acid profile in the liver and muscles; modulate the somatotropic axis gene expression in fetuses from underfed ewes [18]; and improve intestinal integrity and energy balance, immune response, and antioxidant defense of IUGR suckling lambs [32].…”
Section: Introductionmentioning
confidence: 99%
“…The chosen doses of Arg (1%) and NCG (0.1%) were based on prior research with ewes and lambs. 3,8,18 Diets were prepared to meet dietary requirements for suckling lambs according to the NRC (2007), 22 and had similar amounts of nitrogen (equilibrated by alanine) and energy. The NCG (at 97% purity) was purchased from Sigma-Aldrich Corporate (St. Louis).…”
Section: Diets With Milk Replacer (Mr)mentioning
confidence: 99%
“…29 The mRNA level of each target gene was expressed relative to the CON group. Although ACTB has been found to have a high degree of stability in similar samples and has been previously used as an internal control gene, 8 we acknowledge that using more than one internal control gene is the most appropriate approach to normalize gene expression data. 30,31 Therefore, we consider that using ACTB as the only internal control gene is a limitation to this study.…”
Section: Mrna Abundance By Real-time Pcrmentioning
confidence: 99%
“…Therefore, NCG supplementation is a novel, effective strategy to improve arginine nutrition. Studies have indicated that NCG supplementation could increase the serum arginine level; improve intestinal growth in intrauterine growth-retarded suckling lambs (10) ; enhance the antioxidant status against oxidative stress in rats (11) ; and increase growth performance in piglets (12) . However, at present, information on the effects of dietary NCG supplementation on body fat deposition is not available.…”
mentioning
confidence: 99%